The Extent of the Relationship between the Dimensions of Customer Relations and the Achievement of Competitive Differentiation: An Applied Study on Egyptian Commercial Banks - Fekry , Mohamed (The Arab Journal of Administration, 2024)
The research aims to show “the extent of the relationship between customer relations dimensions and achieving competitive differentiation” a field study on Egyptian commercial banks, through a main hypothesis: There is a positive, statistically significant effect of the extent of the relationship between customer relations dimensions in achieving competitive differentiation in Egyptian commercial banks. main into three sub-hypotheses: There is a positive, statistically significant effect of customer relationship management and excellence in cost reduction. There is a positive, statistically significant effect between customer relationship management and product quality excellence. There is a positive, statistically significant effect of customer relationship management and excellence in innovation and renewal. The research community consists of all employees of the commercial banks under study, who numbered 49,142 individuals, and then used the sampling method, so that the appropriate size of the sample was determined to be 381 individuals. The research reached several results, the most important of which are: Acceptance of the main hypothesis “there is a positive, statistically significant effect of customer relations dimensions related to each of the focus on major customers, customer relationship management technology, and human resources for customer relationship management on the competitive differentiation of commercial banks.” Acceptance of the first sub-hypothesis, which states that “there is a positive, statistically significant effect of customer relations dimensions on excellence in cost reduction”. Acceptance of the second sub-hypothesis, which states that “there is a positive, statistically significant effect of customer relations dimensions on product excellence”. Acceptance of the third sub-hypothesis, which states that “there is a positive, statistically significant effect of customer relations dimensions on excellence in innovation and renewal.”